Pengaruh Pemberian Beberapa Jenis Pupuk Kandang dan Nutrisi Saputra Terhadap Pertumbuhan dan Hasil Tomat (Lycopersicum esculentum Mill.) Varietas Permata - Noor Jannah; Abdul Patah; Muhtar Muhtar (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2012)
The objective of the research is to study the effect of Manure and Nutrisi Saputra fertilizers as well as their interaction on the growth and yielf of tomato plant and to find out the kind of manure fertilizers and Nutrisi Saputra concentration that affect high yield of tomato plant.The research was carried out in Experiment Garden of Agriculture Faculty University of 17 Agustus 1945 Samarinda. It lasted for three months (August 2009 to October 2009). The Completely Randomized Design was employed applied for this research with factorial analysis 3 x 4 and 5 replications. The first factor was kind of manure fertilizer (K) consisted of 3 levels : no manure fertilizer (k0), chicken manure 1 kg polybag-1 (k1), and cow manure 1 kg polybag-1 (k2); and the second factor was the formulasi on Nutrisi Saputra (N) consisted of 4 levels : no Nutrisi Saputra (n0), 0,5 ml liquid : 1,5 g powder : 2,5 liter water (n1); 1 ml liquid : 3 g powder : 5 liter water (n2), and 1,5 ml liquid : 4,5 g powder : 7,5 liter water (n3). Results of research that the kind of manure fertilizer and concentration of Nutrisi Saputra as well as their interaction affected significantly to very significantly on the growth and yielf of tomato plant. The highest production of fruit was attained on combination of chicken manure fertilizer 1 kg polybag-1 and formulasi of Nutrisi Saputra 0,5 ml liquid: 1,5 g powder: 2,5 liter water namely 62,00 g plant-1.